Accelerated gross nitrogen cycling following garlic mustard invasion is linked with abiotic and biotic changes to soils - Edwards, Joseph D.; Cook, Allison M.; Yannarell, Anthony C.; Yang, Wendy H. (Frontiers in Forests and Global Change, 2022)
Alliaria petiolata (garlic mustard), an invasive forest herb in North America, often alters nutrient availability in its non-native ecosystems, but the mechanisms driving these changes have yet to be determined. We hypothesized three potential mechanisms through which garlic mustard could directly influence soil nitrogen (N) cycling: by increasing soil pH, by modifying soil microbial community composition, and by altering nutrient availability through litter inputs. To test these hypotheses, we evaluated garlic mustard effects on soil pH and other soil properties; fungal and prokaryotic (bacterial and archaeal) community composition; and soil N cycling rates (gross N mineralization and nitrification rates, microbial N assimilation rates, and nitrification- versus denitrification-derived nitrous oxide fluxes); and we assessed correlations among these variables. We collected soil samples from garlic mustard present, absent, and removed treatments in eight forests in central Illinois, United States, during the rosette, flowering, and senescence phenological stages of garlic mustard life cycle. We found that garlic mustard increased soil pH, altered fungal and prokaryotic communities, and increased rates of N mineralization, nitrification, nitrification-derived net N2O emission. Significant correlations between soil pH and microbial community composition suggest that garlic mustard effects on soil pH could both directly and indirectly influence soil N cycling rates. Correspondence of gross rates of N mineralization and nitrification with microbial community composition suggest that garlic mustard modification of soil microbial communities could directly lead to changes in soil N cycling. We had expected that early season, nutrient-rich litter inputs from mortality of young garlic mustard could accelerate gross N mineralization and microbial N assimilation whereas late season, nutrient poorer litter inputs from senesced garlic mustard could suppress N mineralization, but we did not observe these patterns in support of the litter input mechanism. Together, our results elucidate how garlic mustard effects on soil pH and microbial community composition can accelerate soil N cycling to potentially contribute to the invasion success of garlic mustard.